2015
DOI: 10.1175/jas-d-14-0381.1
|View full text |Cite
|
Sign up to set email alerts
|

Wave-Induced Boundary Layer Separation in the Lee of the Medicine Bow Mountains. Part II: Numerical Modeling

Abstract: Mountain waves and rotors in the lee of the Medicine Bow Mountains in southeastern Wyoming are investigated in a two-part paper. Part I by French et al. delivers a detailed observational account of two rotor events: one displays characteristics of a hydraulic jump and the other displays characteristics of a classic leewave rotor. In Part II, presented here, results of high-resolution numerical simulations are conveyed and physical processes involved in the formation and dynamical evolution of these two rotor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…In this case, the key wave‐ducting mechanism is related to the presence of a sharp density discontinuity collocated with the jet. These findings are consistent with recent real‐case observations of rotor formation in conjunction with a hydrostatic wave‐breaking event (French et al ; Grubišić et al ).…”
Section: Discussionsupporting
confidence: 92%
“…In this case, the key wave‐ducting mechanism is related to the presence of a sharp density discontinuity collocated with the jet. These findings are consistent with recent real‐case observations of rotor formation in conjunction with a hydrostatic wave‐breaking event (French et al ; Grubišić et al ).…”
Section: Discussionsupporting
confidence: 92%
“…Prior to T‐REX, in January and February 2006, the NASA Winter Orographic Clouds Experiment (NASA06) was conducted over the Medicine Bow Mountains (MBM) in southeastern Wyoming, deploying UWKA and WCR in a moist midlatitude wintertime environment. Recently, French et al () and Grubišić et al () provided a detailed analysis of two NASA06 events exhibiting large‐amplitude mountain waves. In their studies, they revealed the presence of large atmospheric rotors and the key role of mid‐tropospheric gravity‐wave breaking in steering the flow dynamics on both days.…”
Section: Introductionmentioning
confidence: 99%
“…Under weak wind shear the rotor produces moderate or severe turbulence. Under stronger shear the rotor is associated with trapped lee waves, in which case the turbulence may be severe [4,20,22,51,52]. Both the WRF simulations and WCR observations suggest that the case presented here was predominantly of the second type.…”
Section: Discussionmentioning
confidence: 74%
“…While the MBM may be rather prone to downslope wind storms [21,22,31], even under marginally strong wind at mountaintop level, they do occur elsewhere (as mentioned in the Introduction), including in more densely populated areas. Most severe wind events in the Boulder, Colorado area, for instance, are associated with downslope wind storms [53].…”
Section: Discussionmentioning
confidence: 99%